Intake assessments of salivary cortisol, survey responses, and adverse childhood experiences are associated with recovery success in an abstinence‐based treatment program for substance use disorders. (25th August 2022) - Maddox‐Rooper, Taylor R.; Sklioutouskaya‐Lopez, Kristiana; Sturgill, Trenton; Fresch, Caroline; Clements, Charles W.; Lamichhane, Rajan; Egleton, Richard; Davies, Todd H.
Abstract: Background: Connecting patients to treatment for a substance use disorder (SUD) that satisfies their needs is often complicated by confounding factors. A reliable measurement of patients' underlying stress level may be helpful because it often reflects many of the same confounders as their SUD. Whereas cortisol levels reflect physiological responses to stress, patients' cortisol levels during recovery from an SUD may serve as biomarkers for stressors that result in poor treatment outcomes, including early discontinuation of treatment. However, further exploration of the relationship between patients' cortisol levels and their treatment outcomes is needed for this approach to be clinically useful. Methods: We enrolled participants from an abstinence‐based, male‐only, residential alcohol and drug recovery program to examine the relationship between salivary cortisol, stress exposure, ACEs, and treatment retention. Results: Participants who remained in the program <90 days had significantly higher initial cortisol levels than those who remained ≥90 days (0.62 ± 0.074 μ g/dl vs. 0.36 ± 0.037 μ g/dl). Kaplan–Meier curves differed significantly when we grouped participants according to whether their cortisol level was below or above the overall average of 0.49 ± 0.044 μ g/dl, with the median numbers of days before discontinuing being 110 and 60, respectively. A Cox proportional hazards model indicated that elevated salivary cortisol (with increases in μ g/dl), marital/relationship status, and adverse childhood experiences (ACEs) score correlated significantly with hazards of discontinuing the program (hazard ratios for the three factors were 3.49, 2.39, and 1.50, respectively). Discussion: Cortisol level may predict, at least partially, SUD treatment program retention regardless of individuals' numerous confounding factors or the substance used. If this approach is validated, it could enable providers to consider patients' cortisol levels at the time of admission to treatment to facilitate their retention in treatment and thereby enhance their recovery. Abstract : Salivary cortisol levels, self‐report survey responses, and Adverse Childhood Experiences were recorded upon intake into an abstinence‐based recovery program to identify factors that associated with early attrition from the program. The study also showed that higher cortisol levels correlated with premature treatment discontinuation as did key survey responses, specific ACEs, and total ACE score also correlated with early attrition. Detecting these factors, particularly the biologic marker, may enable proactive resource allocation for more effective SUD treatment.